Analisis Kinerja Keuangan Koperasi Mikro di Kabupaten Semarang: Objek Studi Koperasi Faomasi Baluse Mandiri - Risman Ndruru; Hendrajaya Hendrajaya (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyse the financial performance and assess the financial health of Koperasi Faomasi Baluse Mandiri in supporting business sustainability. The problem focuses on the condition of liquidity, solvency, and profitability ratios and their implications for operational stability and business development. To approach this issue, the study applies financial ratio analysis theory and cooperative health principles. Data were collected through financial report documentation, interviews with management and supervisors, and observation, and were analysed qualitatively with the support of financial ratio calculations. The findings indicate that the cooperative demonstrates good liquidity, a manageable capital structure despite relatively high dependence on members’ funds, and the ability to generate stable net surplus. Governance practices and internal supervision mechanisms further strengthen its financial condition. This study concludes that sound financial performance and adequate governance are essential factors in maintaining the sustainability of Koperasi Faomasi Baluse Mandiri, although strengthening internal capital and improving administrative systems remain necessary for long-term resilience.